The Impact of Military and Nonmilitary Experiences on Marriage: Examining the Military Spouse's Perspective. Issue 5 (19th October 2018) - Pflieger, Jacqueline C.; LeardMann, Cynthia A.; McMaster, Hope S.; Donoho, Carrie J.; Riviere, Lyndon A.; ,
Abstract: There has been conflicting research regarding direct association between deployments and marital quality, particularly from the military spouse's perspective. In the current study, we sought to extend past research by examining the direct association between both military and nonmilitary experiences and military spouse marital quality using 2011–2013 baseline data from the Millennium Cohort Family Study, a large sample of military couples representing all U.S. service branches and components. Military experiences were assessed using electronic deployment records to capture the number and length of deployments since 2001, and service members reported combat experience and symptoms indicative of posttraumatic stress disorder (PTSD). Military spouses reported on service members' recent time away from home, nonmilitary family stressors, and marital quality. Results of the logistic regression model adjusted for demographic, relationship, and military covariates indicated that most military experiences did not have a direct statistical association with low marital quality except service member PTSD, odds ratio ( OR ) = 1.54, 95% CI [1.17, 2.04]. Rather, nonmilitary experiences of the military spouse, including lack of social support, OR = 2.68, 95% CI [2.07, 3.47]; caregiver burden, OR = 1.56, 95% CI [1.22, 1.99]; work–family conflict, OR = 1.42, 95% CI [1.18, 1.69]; and financial strain, OR = 1.27, 95% CI [1.03, 1.55], increased odds of low marital quality. Implications of these findings include providing additional supports to address nonmilitary family stressors that are particularly salient to military spouses with an aim to promote marital quality. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) El impacto de experiencias militares y no militares en el matrimonio: Examinando la perspectiva del cónyuge militar. CALIDAD DEL MATRIMONIO EN CÓNYUGE MILITAR. Ha habido investigaciones conflictivas que establecen una asociación directa entre despliegues militares y la calidad marital, particularmente desde la perspectiva del cónyuge militar. En el presente estudio, buscamos extender la investigación pasada examinando la asociación directa entre experiencias militares y no militares y la calidad marital del cónyuge militar usando datos de referencia de 2011–2013 del Estudio de la Familia Cohorte del Milenio, compuesto por una amplia muestra de parejas militares que representan a todas las ramas y componentes del servicio militar de E.E.U.U. Las experiencias militares fueron evaluadas usando registros electrónicos de despliegues para capturar el número y la duración de despliegues desde 2001, y los miembros del servicio informaron sobre la experiencia de combate y los síntomas indicativos de trastorno de estrés postraumático (TEPT). Los cónyuges militares informaron sobre el tiempo reciente en que los miembros del servicio estuvieron fuera de casa, los factores no militares de estrés familiar y la calidad conyugal. Los resultados del modelo de regresión logística ajustado para las covariables demográficas, de relación y militares indicaron que en la mayoría de las experiencias militares no tuvieron una asociación estadística directa con la baja calidad marital, con la excepción de TEPT de un miembro del servicio, odds ratio ( OR ) = 1.54, IC 95% [1.17, 2.04]. Más bien, las experiencias no militares del cónyuge militar, incluida la falta de apoyo social, OR = 2, 68, 95% CI [2.07, 3.47]; carga del cuidador, OR = 1.56, IC del 95% [1.22, 1.99]; conflicto trabajo‐familia, OR = 1, 42, IC del 95% [1, 18, 1, 69]; y la tensión financiera, OR = 1.27, IC 95% [1.03, 1.55], incrementa las probabilidades de baja calidad marital. Las implicancias de estos hallazgos incluyen proporcionar apoyos adicionales para abordar los factores no militares de estrés familiar que son particularmente importantes para los cónyuges militares con el objetivo de promover la calidad matrimonial. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 The impact of military and nonmilitary experiences on marriage: Examining the military spouse's perspective Traditional Chinese 標題: 服役與非服役經歷對婚姻的影響:檢視軍人伴侶的觀點 撮要: 過往有關服役與婚姻質素的直接關連研究, 特別是檢視到軍人伴侶觀點的, 都呈現矛盾結果。本研究旨在延伸過往的研究, 檢視服役與非服役經歷跟軍人伴侶婚姻質素的直接關連。我們利用2011–2013年千禧世代家庭研究的基線數據, 當中的大型樣本為來自各個美國軍事部門的軍人夫婦。我們利用電子服役紀錄, 取得樣本自2001年起的服役次數和為期數據, 並從軍人的報告取得戰鬥經歷和象徵創傷後壓力症(PTSD)的症狀數據。軍人伴侶則報告軍人最近一次離家的為期長度、非服役相關的家庭壓力源和婚姻質素。我們對從邏輯迴歸模型得出的結果, 因應人口變量、關係和軍事共變量作調節後, 發現大多數服役經歷跟婚姻質素低並無直接的統計性關連, 除了軍人患PTSD以外(勝算比 (OR) = 1.54, 95% CI [1.17, 2.04])。反而, 軍人伴侶的非服役經歷, 包括欠缺社會支持(OR = 2.68, 95% CI [2.07, 3.47])、作為照顧者的負擔(OR = 1.56, 95% CI [1.22, 1.99])、工作與家庭需要的衝突(OR = 1.42, 95% CI [1.18, 1.69])、以及經濟困難(OR = 1.27, 95% CI [1.03, 1.55]), 加強了婚姻質素低的機會。我們基於結果的建議, 包括提供額外支援, 處理對軍人伴侶影響特別顯著的非服役相關家庭壓力源, 以提升他們的婚姻質素。 Simplified Chinese 标题: 服役与非服役经历对婚姻的影响:检视军人伴侣的观点 撮要: 过往有关服役与婚姻质素的直接关连研究, 特别是检视到军人伴侣观点的, 都呈现矛盾结果。本研究旨在延伸过往的研究, 检视服役与非服役经历跟军人伴侣婚姻质素的直接关连。我们利用2011–2013年千禧世代家庭研究的基线数据, 当中的大型样本为来自各个美国军事部门的军人夫妇。我们利用电子服役纪录, 取得样本自2001年起的服役次数和为期数据, 并从军人的报告取得战斗经历和象征创伤后压力症(PTSD)的症状数据。军人伴侣则报告军人最近一次离家的为期长度、非服役相关的家庭压力源和婚姻质素。我们对从逻辑回归模型得出的结果, 因应人口变量、关系和军事共变量作调节后, 发现大多数服役经历跟婚姻质素低并无直接的统计性关连, 除了军人患PTSD以外(胜算比 (OR) = 1.54, 95% CI [1.17, 2.04])。反而, 军人伴侣的非服役经历, 包括欠缺社会支持(OR = 2.68, 95% CI [2.07, 3.47])、作为照顾者的负担(OR = 1.56, 95% CI [1.22, 1.99])、工作与家庭需要的冲突(OR = 1.42, 95% CI [1.18, 1.69])、以及经济困难(OR = 1.27, 95% CI [1.03, 1.55]), 加强了婚姻质素低的机会。我们基于结果的建议, 包括提供额外支持, 处理对军人伴侣影响特别显著的非服役相关家庭压力源, 以提升他们的婚姻质素。